Safety study of leucoreduced allogeneic pooled freeze-dried platelet-rich plasma in healthy equine joints - Kooy, Sarah; Constant, Jemma; Cole, Robert; Boone, Lindsey (Frontiers in Veterinary Science, 2025)
IntroductionClinical use of blood-derived intra-articular therapies, such as platelet-rich plasma (PRP), have increased in equine athletes due to their proposed disease-modifying effects. Need for a shelf-stable, allogeneic PRP product with known composition for standardized treatment exists. The objective of this study was to compare systemic and local effects of a single intra-articular injection of equine leucoreduced allogeneic pooled freeze-dried PRP (alloPRP) to a placebo control (saline) in normal, healthy equine joints.MethodsTwelve healthy horses were randomly assigned to either control (saline) or treatment (alloPRP) (n = 6 horses per group). The study used a blinded 2-period, 2-treatment, 2-joint non-crossover experimental design. Each study period was defined as 1 week, followed by a 2-week washout between study periods. One joint (radiocarpal or tarsocrural joint) was treated and evaluated per study period. Treatment sequence and limbs chosen for treatment were randomized for each horse. Systemic effects were measured at different time points by physical examination, bloodwork (complete blood count and serum biochemistry), and lameness examination (subjective and objective). Local effects to the joint measured at different time points included heat, swelling, joint circumference, and response to passive flexion as well as synovial fluid analysis. Data was analyzed using linear mixed models with significance set at p < 0.05.ResultsThere were no differences between groups for joint swelling (p = 0.40), joint circumference (p = 0.55), heat scores (p = 0.09), or passive flexion (p = 0.70) following intra-articular injections. Both subjective and objective lameness scores were no different on any study day for both treatment (p = 0.47) and control groups (p = 0.31). There were no differences in complete blood count or serum biochemistry values between groups. No difference in synovial fluid TNCC (p = 0.80), TP (p = 0.94), or synovial fluid concentrations of TNFα (p = 0.45) and IL-1raP (p = 0.18) were observed between groups for each sampled time point (T0 and T7d).ConclusionThe alloPRP formulation was demonstrated to be safe for use in equine joints. Further investigation is necessary for evaluation of clinical efficacy.